Kasi's Crepuscular Rails: revisiting narrative experiences of iStimela in the Pretoria-Witwatersrand-Vereeniging Area - Phahladira, Lesiba (My University, 2021)
Metrorail township commuter trains have significantly become fossils of ‘haunted’ socio-economic experiences of migrant labour, apartheid and memory-making. The township (and) trains are here considered sites and sights for painful volatile memories. With this research, I intend to show continuities and discontinuities of apartheid oppressive policies through post-1994 South Africa’s inheritance of untransformed colonial infrastructure. Commuters, I argue are forced to negotiate personal risk and safety, to endure perpetually degrading apartheid-inherited township train services. Post-apartheid South Africa class in equality proves to have progressively replaced race in reinforcing apartheid urban spatial structures and marginalising the poor. The historical racial subjection of the African has been systematically coupled with dispossession of Africans’ economic viability resulting in the (post-)apartheid poor being largely African. This has created a doubleton of blackness and underprivilege sentencing black livelihoods to abject inconspicuousness. Post-apartheid public disservices like township Metrorail have now become boundaries to a class-stratified society. Like apartheid services were once racially prioritised, post-apartheid services take precedence to upper middle class and the wealthy. Poor commuters in response utilise their everyday experience of frustrations and annoyance to disrupt class and space of former apartheid cities. They employ precarious non-compliant and violent forms of protest to confront their dislocation in the post-apartheid state infrastructure priorities. In this narration, isparapara train boarding and mangobe were found to be a conflicted rejection of residues of persisting post-apartheid unequal black township and white city train classes
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Faculty of Humanities, University of the Witwatersrand, 2021